China and East Asian production networks: some policy implications. (14th April 2009) - Thorpe, Michael
The integration of the East Asian economies has grown markedly over the past decade as a result of the expansion in regional production and distribution networks involving the machinery industry. A significant triangular pattern of trade has emerged, with Japan and the newly industrialised economies exporting intermediate goods to the ASEAN-4 countries and (increasingly) China for processing and re-exporting to Europe and North America. While China has emerged as the key link in this chain, it is also seen as a major export competitor for regional economies in third markets. An understanding of the nature and changing pattern of regional trade and investment flows is necessary for effective policy formulation by regional governments in East Asia.